Discovery of oxime-bearing naphthalene derivatives as a novel structural type of Nrf2 activators. Issue 13 (1st July 2015) - Chang, Ken-Ming; Liang, Fong-Pin; Chen, I-Li; Yang, Shyh-Chyun; Juang, Shin-Hun; Wang, Tai-Chi; Chen, Yeh-Long; Tzeng, Cherng-Chyi
Graphical abstract: Abstract: Recent studies have demonstrated that oxidative stress insult is one of major causes of tumor formation. Therefore, identify the effective anti-oxidative agents as a preventive approach to stop cancer progression has widely explored. Although, many potent anti-oxidative ingredients in the natural products have been identified but the amount from the nature source hindrances the clinical application. Compound which can activate Nrf2 signaling pathway result unregulated the cellular antioxidant-responses has been demonstrated as an effective chemopreventive approach for cancer treatment. In the present study, certain oxime-bearing naphthalene derivatives were synthesized and evaluated for their Nrf2 activation and anti-proliferative activities. Results indicated ( E )-1-(naphthalen-2-yloxy)propan-2-one oxime (11 ) which increased 2.04-fold Nrf2/ARE-driven luciferase activity was more active than its 1-substituted isomer10 (1.17-fold) and t -BHQ (1.77-fold), the known Nrf2 activator. The activities were further increased by the replacement of the peripheral methyl group with the phenyl ring in which ( Z )-2-(naphthalen-2-yloxy)-1-phenylethanone oxime (13a ) exhibited 3.49-fold potency of the positive control. It is worth to mention that compounds11, 13a, and13b which showed significant Nrf2 activation are non-cytotoxic to the tested cells with IC50  > 50 μM. This observation strongly suggested that these compounds can be used for chemoprevention. Mechanism studies indicated that these compounds were capable of inducing the phosphorylation of Nrf2 protein at serine 40 which led to the activation of the Nrf2 transcriptional activity.